(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Hepatitis B is a viral infectious disease that affects the liver and can occur in acute or chronic forms. According to WHO estimates, in 2022 there were 254 million people worldwide living with chronic hepatitis B, with approximately 1.2 million new infections occurring each year. Hepatocellular carcinoma (HCC) is the most common primary malignant tumor of the liver, resulting from malignant transformation of hepatocytes. It is estimated that in 2022 about 1.1 million people died from hepatitis, mainly due to liver cirrhosis and hepatocellular carcinoma (primary liver cancer).